Dampak Pelatihan, Penempatan dan Kemampuan Terhadap Kinerja Karyawan - Nizamuddin (Journal of Trends Economics and Accounting Research, 2023)
The analysis of the research aims to find out whether training, placement, and abilities, partially and simultaneously, have a positive and significant impact on the performance of Grand City Hall Field employees. The data analysis technique used is an associative method with the help of the SPSS program version 26.0. This study uses double linear regression analysis. The sample in this study was 59 respondents. Primary data collection using a questionnaire. The results of the study showed that training had a partial effect on the performance of Grand City Hall Field employees where the score was 2,125 > table 1,673 and significantly 0,003 < 0,05. The placement had an partial impact on performance of grand city hall staff where the rating was 2,555 > table 1 673 and the significance was 0,001 < 0,055. Capacity had a Partial influence on performance for Grand city hall field employees where it was 5,018 > ttabe1,673, significantly 0.001 < 0.05. Training, placement, and capabilities simultaneously had an impact on Grand city Hall Field staff performance where the coefficient value was > 169,388 > 2.79 at a significant 0.00 < 0.05.